Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Liana Illiyanti; Abdul Malik; Bambang Kurniawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The background of this research is the decline and fluctuation in each research variable, especially the company value variable which has decreased drastically from the previous year. This study aims to determine the effect of financial performance on the value of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for 2016-2021. This study uses a quantitative approach with secondary data collection methods. The analytical method used in this research is multiple linear regression analysis. The samples used in this study were 11 companies taken by purposive sampling method. The results of this study indicate that the variable liquidity has a significant negative effect on firm value. Meanwhile, the leverage and profitability variables have a positive and significant effect on firm value. This study also shows that together the variables Liquidity, Leverage and Profitability have a joint effect on company value in Food and Beverage Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2016-2021.